2013
DOI: 10.1016/j.neuroimage.2013.04.089
|View full text |Cite
|
Sign up to set email alerts
|

Local mechanical properties of white matter structures in the human brain

Abstract: The noninvasive measurement of the mechanical properties of brain tissue using magnetic resonance elastography (MRE) has emerged as a promising method for investigating neurological disorders. To date, brain MRE investigations have been limited to reporting global mechanical properties, though quantification of the stiffness of specific structures in the white matter architecture may be valuable in assessing the localized effects of disease. This paper reports the mechanical properties of the corpus callosum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
156
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(174 citation statements)
references
References 51 publications
18
156
1
1
Order By: Relevance
“…Data from five repeated examinations of a healthy volunteer are available for both 50 Hz external actuation 40,43 and 1 Hz intrinsic actuation. 11 The IA subject was a 51 yr old male and the five MRE datasets were acquired over a 22 month period, whereas the EA subject was a 24 yr old male and the MRE data were acquired over a two month period.…”
Section: A Viscoelastic and Poroelastic Inversions Of Ea And Ia Brmentioning
confidence: 99%
“…Data from five repeated examinations of a healthy volunteer are available for both 50 Hz external actuation 40,43 and 1 Hz intrinsic actuation. 11 The IA subject was a 51 yr old male and the five MRE datasets were acquired over a 22 month period, whereas the EA subject was a 24 yr old male and the MRE data were acquired over a two month period.…”
Section: A Viscoelastic and Poroelastic Inversions Of Ea And Ia Brmentioning
confidence: 99%
“…MRE is also being increasingly used for presurgical evaluation of meningioma consistency [26,27]. Our group has significant experience in the design and application of MRE methodology for studying the human brain in vivo [6,9,10,28,29]. Previously, we demonstrated that viscoelastic property measures derived from brain MRE are very reliable with coefficients of variation from repeated measurements in the order of 5% [6].…”
Section: Discussionmentioning
confidence: 99%
“…Our group has significant experience in the design and application of MRE methodology for studying the human brain in vivo [6,9,10,28,29]. Previously, we demonstrated that viscoelastic property measures derived from brain MRE are very reliable with coefficients of variation from repeated measurements in the order of 5% [6]. A recent repeatability study using the same methodology as in this work found the coefficient of variation for cerebral stiffness to be less than 2% [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations